The Relationship Between Vegetarian Diet and The Risk of Coronary Heart Disease - A. Andrianto; R. I. Gunadi (Universitas Airlangga, 2020)
Background. Coronary heart disease (CHD) is a major cause of death in developed countries whereas most cases can be prevented by addressing behavioral risk factors, such as unhealthy diet. Vegetarian dietary patterns reduce CHD risk and mortality by 40%. The Framingham Heart Study on Hard CHD calculates a 10-year risk assessment with six predictors, two of which are lipid profile types. Aims. To discover the relationship between vegetarian diet and the risk of coronary heart disease, we did a cross-sectional analytical observation in North Jakarta using 30 healthy vegetarians and 30 healthy non-vegetarians aged of 20-34 years in 2010. Framingham Heart Study on Hard CHD 10-year risk assessments were done on both groups. Methods. Results were compared and analyzed using Mann-Whitney U and Spearman correlation tests. Results. Mann-Whitney U test showed significant differences on total cholesterol and total FHS risk points (p-value 0.000; pvalue 0.000). Spearman correlation analysis on total risk points confirms a moderate negative degree for vegetarian diet and CHD risk (r = -0.525, p-value 0.000). In conclusion, there is a significant relationship between vegetarian diet and a reduced risk of coronary heart disease in 20-34 years of age.